Comparison of the prevalence of Cocoa Swollen shoot virus and the prevalence of Phytophthora sp in Petit-Bondoukou, South-West of Côte d’Ivoire - Oro, Franck Zokou; Lallie, Hermann-Desiré; Koné, Nahoua; Kouadio, Juslin; Diallo, Hortense Atta (International Journal of Environment, Agriculture and Biotechnology, 2021)
Background: Swollen shoot and Black pod disease are two major diseases that cause significant damage in Nawa region. In order to compare the prevalence of these two diseases, a study was conducted in Soubré area in the south-west of Côte d'Ivoire, at the site of Petit-Bondoukou. Methods: The observation system consists of a sentinel site of approximately 10 km X 10 km. Each sentinel site is made up of 16 clusters of 2.5 km X 2.5 km containing about 10 plots which constitute the different observation points. In this study, observations were made in 4 plots of the site. The variables that were measured during data collection were the total number of pods on each tree, the total number of pods with black pod disease symptoms and the total number of diseased trees in the swollen shoot outbreaks. The prevalence of each pathogen was deduced from the measured variables and then related using the Bravais-Pearson correlation test. Beforehand, a molecular analysis was carried out to identify the different species of Phytophthora. Results: The results of the molecular analysis showed that the only species identified at this site was Phytophthora palmivora. The descriptive analysis showed that the prevalence of CSSV was higher than that of Black pod disease with 50% and 32% respectively. Statistical analysis showed that there is a positive and significant correlation between the prevalence of swollen shoot and black pod disease. Conclusion: This study shows that most of the test trees at the site of Petit-Bondoukou show both Swollen shoot and Black pod disease symptoms and invites growers contribute to reducing the pressure of both diseases by leading regular activities plot maintenance.